2002
DOI: 10.1002/1521-3935(200210)203:14<2042::aid-macp2042>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation of partially norbornylized linseed oil

Abstract: Epoxidation of linseed oil was performed with peracetic acid formed in situ by the reaction of hydrogen peroxide and acetic acid in the presence of Amberlite 120H as catalyst, and toluene as solvent. Some variables were evaluated as temperature and the molar ratio and solution of aqueous hydrogen peroxide (30 and 50 wt%) for obtaining a maximum of yield and conversion of epoxidized oil. The characterization of conversion of double bonds (DB) to epoxy ring, the relative percentage of epoxidation and selectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…IR spectra of LO and PO reveal the presence of characteristic absorption bands for H C C H stretching, C C , CH 2 , CH 3 assymmetrical, CH 2 , CH 3 symmetrical, C C( O) O and O C C ester (Table 1). 1 H NMR spectra of LO and PO are also comparable, just as in other vegetable oils, showing 9-10 different signals of varying intensity attributed to the protons of triacylglycerol. However, considerable variation in peak intensity of signals of protons attached to double bonds is observable owing to their varying extent of unsaturation.…”
Section: Spectral Analysesmentioning
confidence: 61%
See 1 more Smart Citation
“…IR spectra of LO and PO reveal the presence of characteristic absorption bands for H C C H stretching, C C , CH 2 , CH 3 assymmetrical, CH 2 , CH 3 symmetrical, C C( O) O and O C C ester (Table 1). 1 H NMR spectra of LO and PO are also comparable, just as in other vegetable oils, showing 9-10 different signals of varying intensity attributed to the protons of triacylglycerol. However, considerable variation in peak intensity of signals of protons attached to double bonds is observable owing to their varying extent of unsaturation.…”
Section: Spectral Analysesmentioning
confidence: 61%
“…It can be accomplished by different approaches such as by using peracetic acid, dioxirane and hydrogen peroxide. Oils such as linseed, soybean, safflower, sunflower, canola, crambe, meadowfoam, lesquerella, rapeseed, rubberseed, castor, tung, coriander, olive and Annona squamosa have been epoxidized by aforementioned agents [1][2][3][4][5][6]. Aliphatic epoxies derived from vegetable seed oils are characterized by good adhesion, flexibility and corrosion resistance properties [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Linseed oil can be chemically modified by epoxidation leading to epoxidized linseed oil (ELO), which is a basic polymer for the production of various plastics worldwide. Chen et al (2002) reported that ELO can be obtained via peracetic acid, dioxirane, or hydrogen peroxide as a catalyst, while hydrogen peroxide seems to be the most efficient oxidizing agent.…”
Section: Introductionmentioning
confidence: 99%
“…In the spectra from hemp oil and the bio-resins, the band at 1741 cm -1 signifies C=O stretching of carboxylic group of fatty acids (peak b). Peak a at wavenumber 3009 cm -1 corresponded to the stretching of C=C double bonds, which are consumed during epoxidation and acrylation (Chen et al 2002;Mungroo et al 2008;Espinoza-Pérez et al 2009). Peak c at 823 cm -1 in the EHO spectrum corresponded to C-O-C stretching in the epoxide ring (Vlcek and Petrovic 2006;Espinoza-Pérez et al 2009;Mustata et al 2011).…”
Section: Ftir Spectroscopymentioning
confidence: 99%